(untitled) (Heritage, 2022)
Various aspects of marital and family life are an important resource for the mental health of adults. The main goal of this research was to examine whether depression, anxiety and stress of adults living in the territory of Kosovo and Metohija can be predicted based on the successful resolution of marital conflicts, marital stability and family satisfaction. The sample consisted of 185 adults, 100 women and 85 men, living in marriage or cohabitation. Several questionnaires were used in the research: Marital Conflict Resolution Success Scale, Marital Stability Scale, Family Adaptation Questionnaire and DASS-21. The obtained results show that the only significant predictor of anxiety, depression and stress was the successful resolution of marital conflicts. There is a moderate to high correlation between the examined aspects of married and family life, so this possibility of their mutual action may be the reason why other changes did not prove to be significant. The obtained results are discussed in the light of relevant theoretical concepts and the results of some earlier researches.